Alice's Adventures In Wonderland and Through The Looking-Glass - CARROLL Lewis Carroll
The Mad Hatter, the Ugly Duchess, the Mock Turtle, the Queen of Hearts, the Cheshire Cat-characters each more eccentric than the last, and that could only have come from Lewis Carroll, the master of sublime nonsense. In these two brilliant burlesques he created tw